Comparative biodistribution studies of technetium-99 m radiolabeled amphiphilic nanoparticles using three different reducing agents during the labeling procedure - Geskovski, Nikola; Kuzmanovska, Sonja; Simonoska Crcarevska, Maja; Calis, Sema; Dimchevska, Simona; Petrusevska, Marija; Zdravkovski, Pance; Goracinova, Katerina (Wiley, 2013)
Considering the confusing biodistribution data through the literature and few reported alerts as well as our preliminary biodistribution results, we decided to evaluate the interaction and interference of the commonly present (99m) Tc (technetium-99m)-stannic oxide colloid during the direct stannous chloride (99m) Tc-labeling procedure and to assess its influence on the biodistribution pattern of amphiphilic poly(lactic-co-glycolic acid) nanoparticles. In order to confirm our thesis, beside stannous chloride, we employed two different reducing agents that don't form colloidal particles. The use of sodium borohydride was previously reported in the literature, whereas sodium dithionite was adapted for the first time in the (99m) Tc direct labeling procedure for nanoparticles. The results in our paper clearly differentiate among samples with and without colloidal impurities originating from the labeling procedure with a logical follow up of the radiochemical, physicochemical evaluation, and biodistribution studies clarifying previously reported data on stannic oxide colloidal interference. (99m) Tc-nanoparticle complex labeled with sodium dithionite as reducing agent illustrated appropriate labeling efficacy, stability, and potential for further use in biodistribution studies thus providing solution for the problem of low-complex stability when sodium borohydride is used and colloidal stannic oxide interference for stannous chloride procedure.